DEVELOPING PACU JALUR ETHNIC BASED CONTEXTUAL MODEL AT ELEMENTARY SCHOOLS - Erlisnawati; Jesi Alexander Alim; Hendri Marhadi; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study was intended to construct a Pacu Jalur ethnic-based contextual model, a learning model developed based on the stages of Pacu Jalur Ethno. This study was a research and development (R&D) study using the Borg & Gall stages. The research was carried out until the product development stage, which involved designing a learning model based on Pacu Jalur Ethno. The resulting product was then validated by experts to determine the appropriateness of the Pacu Jalur Ethno-based contextual model for classroom use. Data were collected through literature review, interviews, observations, and documentation. Based on the findings, the Pacu Jalur Ethno-based contextual model was deemed suitable for implementation in the learning process using the following syntax: stage 1, planning (merencanakan); stage 2, doing the tasks (membuek jalur); stage 3, discussion (bapacu); and stage 4, closing (panutuik). The Pacu Jalur ethnic-based contextual model illustrated that learning activities could integrate local wisdom relevant to the environment where the learning took place. Consequently, the learning process became more concrete by linking concepts to students’ daily lives.